ASIC and ENaC type sodium channels: conformational states and the structures of the ion selectivity filters. (15th September 2016) - Hanukoglu, Israel
Abstract : The acid‐sensing ion channels (ASICs) and epithelial sodium channels (ENaC) are members of a superfamily of channels that play critical roles in mechanosensation, chemosensation, nociception, and regulation of blood volume and pressure. These channels look and function like a tripartite funnel that directs the flow of Na + ions into the cytoplasm via the channel pore in the membrane. The subunits that form these channels share a common structure with two transmembrane segments (TM1 and TM2) and a large extracellular part. In most vertebrates, there are five paralogous genes that code for ASICs (ASIC1–ASIC5), and four for ENaC subunits alpha, beta, gamma, and delta (α, β, γ, and δ). While ASICs can form functional channels as a homo‐ or heterotrimer, ENaC functions as an obligate heterotrimer composed of α‐β‐γ or β‐γ‐δ subunits. The structure of ASIC has been determined in several conformations, including desensitized and open states. This review presents a comparison of the structures of these states using easy‐to‐understand molecular models of the full complex, the central tunnel that includes an outer vestibule, the channel pore, and ion selectivity filter. The differences in the secondary, tertiary, and quaternary structures of the states are summarized to pinpoint the conformational changes responsible for channel opening. Results of site‐directed mutagenesis studies of ENaC subunits are examined in light of ASIC1 models. Based on these comparisons, a molecular model for the selectivity filter of ENaC is built by in silico mutagenesis of an ASIC1 structure. These models suggest that Na + ions pass through the filter in a hydrated state. Abstract : ASICs and epithelial sodium channels (ENaC) are members of a superfamily of nonvoltage‐gated ion channels that play critical roles in neural sensation, electrolyte homeostasis, and blood pressure regulation. This review presents a comparison of the secondary, tertiary, and quaternary structures of ASIC conformational states. Models of ASIC and ENaC selectivity filters suggest that Na + ions pass through the filter in a hydrated state.